Synthesis, crystal and electronic structure, anticancer activity of ruthenium(II) arene complexes with thiosemicarbazones. (11th April 2013) - Su, Wei; Zhou, Quan; Huang, Yanmin; Huang, Qianyang; Huo, Lini; Xiao, Qi; Huang, Shan; Huang, Chusheng; Chen, Rui; Qian, Quanquan; Liu, Lifeng; Li, Peiyuan
<x xml:space="preserve">Abstract</x> A series of half‐sandwich ruthenium(II) arene complexes [(η6‐p‐cymene)RuII(R‐BzTSC)Cl]Cl 111 (BzTSC = benzaldehyde thiosemicarbazone and R = H, CH3 and C6H5) have been synthesized and characterized by IR, 1H NMR, UV‐visible, electrospray ionization mass spectrometry and elemental analysis. The single‐crystal structures of 1 and 1 have been determined. The molecular orbitals and electronic absorption spectra of the compounds have been calculated using the DFT and TDDFT methods. The in vitro antiproliferative activities of these complexes have been evaluated against four human cancer cell lines (CNE, H292, SKBR3 and Hey1‐B), and 1 is proved to be the most efficient inhibitor, with IC50 values of 20, 31, 10 and 34 μm, respectively. Copyright © 2013 John Wiley & Sons, Ltd.